(untitled) (Fiep Bulletin - online, 2011)
Introduction: The subject of university extension has been occupying an increasingly larger space in the activities of Brazilian universities. In order to qualify for a teaching / learning process of students of Nursing College of Health Sciences, Trairi (FACISA), promote the improvement of population health by developing educational and scientific research, contribute to the strengthening of Health System (SUS), to promote continuing education of professionals working in them, and keep the training areas of practice, strengthening the link teaching and community service, created the extension project entitled "Epidemiology and Environmental Health in the context of the Unified Health System." Objective: To know the perception of university students, participants of the extension project epidemiology and environmental health in the context of SUS on the importance of their training. Methodology: This article was developed from the analysis, a qualitative approach, on the theme of the performance of students in poor communities, through the university extension project epidemiology and environmental health in the context of the SUS FACISA in Santa Cruz / RN / Brazil. The population consisted of 15 students FACISA. As data collection instrument used an interview guide with questions structured. The data were subjected to content analysis. Results: The categories that emerged from the discourse of the interviewees about the importance of participation in the extension project for the training were to find the actual social interaction with the community, developing skills for the implementation of health actions. Conclusion: The university extension facilitates the formation of national and professional accreditation, increasingly, in the society as a privileged space of knowledge production significantly to overcoming social inequalities.